Kebijakan Penyaluran Beras Sejahtera Madani di Kelurahan Pematang Pasir Kecamatan Teluk Nibung Kota Tanjungbalai - Sirait, Masitoh; Warjio, Warjio; Kadir, Abdul (Universitas Medan Area, 2019)
The purpose of this study is to describe the supporting and inhibiting factors in the implementation of the Madani Prosperous Rice Program in Pematang Pasir Subdistrict, Teluk Nibung Subdistrict, Tanjungbalai City. This research method uses qualitative research with a descriptive-analytical approach. The results showed that the limited time at the planning stage caused the implementation of Madani Prosperous Rice program to be